AN INNOVATIVE METHODOLOGY FOR DEVELOPING SPATIAL COGNITION THROUGH THE INTEGRATION OF DESCRIPTIVE GEOMETRY AND PERSPECTIVE DRAWING - Yuldashev Solmonjon Iqboljon ugli (Bright Mind Publishing, 2025)
This scientific article investigates an innovative methodology for developing students' spatial thinking through the integration of Descriptive Geometry and Perspective Drawing. The research introduces and tests instructional strategies grounded in modern digital technologies such as AutoCAD, SketchUp, Blender, and virtual reality. Comparative analysis between control and experimental groups demonstrated significant improvements in spatial cognition among students engaged with digital and project-based methods. The article emphasizes interdisciplinary teaching, STEAM principles, and metacognitive strategies through enhanced instructional modules. The study concludes by recommending the creation of a national model for spatial thinking education within Uzbekistan’s higher education system.
Keywords: Descriptive geometry, perspective drawing, spatial cognition, digital technologies, AutoCAD, visual literacy, STEAM, project-based learning, educational innovation.